A Grammar of Kilmeri. - Gerstner-Link, Claudia (Pacific Linguistics PL Ser., 2018)
This book is a description of Kilmeri, a language of Papua New Guinea, based on the author's fieldwork. The volume is dedicated to the detailed description of form and meaning and their interface, which is supported through extensive illustration by examples. The narrative structure of entire texts is accessible via a small collection of fully glossed personal and traditional stories included in the Online Supplement. The typological evaluation of selected properties of Kilmeri rounds out the description of the language.